Legal Efforts to Settle the Problem of Transfer of Home Ownership Credit Under Hand Between the Debtor and a Third Party (Case Study Decision Number 61/Pdt.P/2022/PN.Kdi) - Fitrawati, Fitrawati (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This research aims to find out, study and analyze the process of private transfer of home ownership credit between the debtor and a third party; to find out, study and analyze the legal consequences of the private transfer of home ownership credit between the debtor and a third party; and to find out, study and analyze legal efforts to resolve the issue of private transfer of home ownership credit between the debtor and a third party. This research method uses a type of normative legal research, with a statutory approach, conceptual approach and case approach. The type and source of data is secondary data, with data sources in the form of primary legal materials, secondary legal materials and tertiary legal materials which are carried out using data collection methods in the form of library studies, documentary studies and interviews. The data obtained is presented in the form of descriptions arranged systematically, logically and rationally, then the data is analyzed using qualitative descriptive analysis methods. The results of this research show that the transfer of home ownership credit under the hands of the debtor and a third party or without the knowledge and approval of the creditor or the bank providing the mortgage, the process does not take long, there is enough agreement between the debtor and the third party, but this action is not justified by the creditor. or is considered an act of default. Resulting in debtors and third parties compensating for losses incurred in the form of money or compensation for losses in the original condition. The legal effort to resolve the KPR transfer problem privately between the debtor and a third party is by taking legal action by filing a lawsuit or decision with the district court. So that the private transfer of home ownership credit between the debtor and a third party which is carried out by means of sale and purchase is declared valid and has permanent legal force regarding the validity of the private sale and purchase.